Preoperative CT angiography versus Doppler ultrasound mapping of abdominal perforator in DIEP breast reconstructions: A randomized prospective study. Issue 6 (June 2015) - Klasson, S.; Svensson, H.; Malm, K.; Wassélius, J.; Velander, P.
Summary: Is there a difference in surgery time and complication rate when Doppler ultrasound (US) is used for the preoperative mapping of perforators in comparison with computer tomography angiography (CTA)? Women who were candidates for breast reconstruction using the deep inferior epigastric perforator (DIEP) free flap were enrolled in a prospective randomized study. The operating time was 249 ± 62 min (mean ± SD) in the CTA group ( n  = 32) and 255 min ± 75 in the US group ( n  = 31) – hence a difference of 6 min on average. No flaps were lost. Sixteen complications occurred in 15 patients: seven in the CTA group and nine in the US group. Complications were remedied without delay and all patients came through with a favorable reconstruction. Preoperative mapping of perforators with US is satisfactory enough provided the microsurgery team has proper experience in breast reconstruction with the DIEP flap.